Family factors and fruit and vegetable consumption in Chinese preschool children living in Hong Kong. Issue 3 (15th November 2018) - Chan, Ruth; Yeung, Suey; Leung, Cynthia; Lo, Sing Kai; Tsang, Sandra
Abstract : Purpose: The purpose of this paper is to examine the association of various family factors with children's fruit and vegetable (FV) intake. Design/methodology/approach: A cross-sectional analysis of data from 601 parent-child dyads with children aged three to six years old was conducted. Parents completed questionnaires on child's FV intake, parenting styles, parental feeding practices, family functioning, television viewing at mealtimes and frequency of family meals. Logistic regression was used to assess the association between various family factors and the likelihood of meeting the child's daily FV recommendation with adjustment for different demographic variables. Findings: Multivariate model adjusting for sociodemographic data indicated that meeting vegetable recommendation was associated with lower frequency of dining with grandparents (Odds ratio (OR) 0.94, 95% confidence interval (CI) 0.89–0.99, p =0.031) and positively associated with parents using more desirable parental feeding practices (OR 1.15, 95% CI 1.09–1.21, p <0.001). Meeting fruit recommendation was associated with parents using more desirable parental feeding practices (OR 1.13, 95% CI 1.09–1.17, p <0.001), higher frequency of dining with grandparents (OR 1.05, 95% CI 1.00–1.10, p =0.041), lower frequency of dining with father (OR 0.89, 95% CI 0.82–0.98, p =0.014) and higher score on authoritative parenting style (OR 1.05, 95% CI 1.01–1.08, p =0.009). Originality/value: This study highlights the potential protective roles of various family factors, in particular authoritative parenting style and parental feeding practices, such as role modeling, moderate restrictive practices for less healthy foods, avoidance of forced feeding, and not using junk food as reward in relation to meeting FV recommendation in children. The role of grandparents in influencing the young children's eating behaviors within the Chinese family warrants further investigation.